1975
DOI: 10.1113/jphysiol.1975.sp011091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ascorbic acid on histamine metabolism in scorbutic guinea‐pigs.

Abstract: SUMMARY1. In guinea-pigs fed an ascorbic-acid-free diet, as the ascorbic acid levels decreased the histamine levels in blood and urine rose steadily to maxima in about 10-12 days. The elevated histamine levels persisted in the blood and urine of scorbutic guinea-pigs and the histamine levels in lung, gastric mucosa and spleen also increased.The increased histamine content of the urine, blood and other tissues in the ascorbic-acid-depleted condition could be brought back to normal levels by administration of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

1978
1978
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 10 publications
0
11
0
2
Order By: Relevance
“…However, this interpretation is complicated due the ability of ascorbate to catalyze the degradation of histamine. Several early studies provided evidence of the histamine degradative potential of ascorbate (Imanaga, 1955a, 1955b; Nandi et al , 1974; Chatterjee & Gupta, 1975; Chatterjee et al , 1975; Subramanian, 1978). Uchida and colleagues later demonstrated that ascorbate degrades histamine through a selective and direct interaction at the imidazole ring (Uchida et al , 1989).…”
Section: Discussionmentioning
confidence: 99%
“…However, this interpretation is complicated due the ability of ascorbate to catalyze the degradation of histamine. Several early studies provided evidence of the histamine degradative potential of ascorbate (Imanaga, 1955a, 1955b; Nandi et al , 1974; Chatterjee & Gupta, 1975; Chatterjee et al , 1975; Subramanian, 1978). Uchida and colleagues later demonstrated that ascorbate degrades histamine through a selective and direct interaction at the imidazole ring (Uchida et al , 1989).…”
Section: Discussionmentioning
confidence: 99%
“…However, direct evidence for a causal relationship between these two parameters is lacking and it is possible that alterations in tissue AsA levels also reflect other detoxification processes during oil exposure. AsA is required for the detoxification of hstamine (Chatterjee et al, 1975). Further, AsA is important in maintaining the redox state of the cell and may act directly to reduce the superoxide anion radical generated during exposure to xenobiotics (Nishikimi, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…It both prevents histamine release and increases the detoxification of histamine (Balz, 2003). According to Chatterjee et al (1975), other varieties of stress conditions, namely; administration of drugs, vaccines, toxoids and physical stress, the formation or release of histamine was increased in rats and guinea-pigs, and the administration of ascorbic acid resulted in detoxification of histamine in the body.…”
Section: Effect Of Vitamin C As An Antihistaminementioning
confidence: 99%